IMPLEMENTASI ASSOCIATION RULE MINING UNTUK MENENTUKAN MENU MAKANAN DENGAN ALGORITMA APRIORI - Henri Pandiangan (Jurnal Mantik Penusa)
Warung Miso Pamatang is a Warung located at Jln. Sudirman No.36, Kel. Teladan, West Siantar, Pematangsiantar City, North Sumatra. This stall is a simple building that looks like a building of an ancient house, the term is like a traditional house. Warung Miso Pamatang (WMP) provides a menu book as a medium for visitors to choose an ordered menu item that lists food and beverage items. The database holds all data related to the activities of consumer purchase transaction data. therefore the writer uses this transaction data using datamining. By using Datamining the Association Rule Mining method, the stored data can be reviewed and processed so that it gets new information. By finding this new information, use the Association Rule Mining method to find combinations of food items and beverage items. Association Rule Mining conducts mining on sales transaction data recorded on the payment receipt printed by the cash register at a certain time period. In conducting Association Rule Mining, the author uses the FIN algorithm. FIN algorithm is a frequent itemset algorithm that uses a novel data structure in the form of nodesets.From some of the descriptions that have been obtained from the results of the discussion in the Implementation of the Mining Rule Association to determine the food menu with the Apriori Algorithm (Case Study of Warung Miso Pamatang, pematangsiantar) can help the owner of the shop where the Warung Miso Pematang owner knows the menu what foods are most often ordered by consumers and easier to see patterns of consumer purchases. With that also the owner of this stall knows which food ingredients should be prepared more to make the food menu that is most in demand by consumers, so that the work carried out runs effectively and efficiently.